Removal of Lead Ions from Water by Struvite Natural Zeolite Composite - Dend, Man-Jun; Wang, Xue-Jiang; Cheng, Xue-Jun; Jing, Huan-Ping; Zhao, Jian-Fu (Huanjing kexue, 2019)
A nitrogen and phosphorus recovery product (NZ-MAP) containing struvite was applied to remove heavy metal ions and lead from water. NZ-MAP was characterized using XRD, FTIR, and SEM/EDS. The effects of dosage, initial pH, and reaction time on the removal process were investigated. The results show that the main component of NZ-MAP is a natural zeolite loaded with struvite. When the dosage is 0.4 g·L , the maximum adsorption amount is 749.74 mg·g , and the adsorption of Pb in the solution increases first and then tends to reach a balance with increase of the pH. Its removal mechanism is mainly Pb (PO ) (OH) precipitation, and the effect is best when pH is 5.0. The removal process of Pb from water is more in line with the quasi-two stage kinetic model. In an investigation of the effect of coexisting heavy metal ions on the removal of lead ions in water by NZ-MAP, it was found that coexisting Ni and Cu have little effect on NZ-MAP adsorption on Pb . Coexisting Zn and Al obviously inhibit the adsorption of Pb by